Efektivitas Model Aktivitas, Refleksi, Konsep, Aplikasi (ARKA) pada Pembelajaran Matematika Sekolah Dasar - Balqis Maharani; Fadliyah Nurbayyinah; Siti Zulfa Nurul Iqomah; Salma Nazihah; Karantiano S. Putra (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Previous studies have proven the success of the Activity, Reflection, Concept, and Application (ARKA) model in religious education, yet its application in exact sciences remains underexplored. Therefore, this study aims to analyze the effectiveness of the ARKA model as a novel strategy in mathematics learning for grades I–III at SD GIS Prima Insani. Effectiveness in this descriptive qualitative study was operationally measured by indicators of learning objective achievement and classroom management changes. Data were collected through observations, interviews, and document reviews involving classroom teachers, mathematics teachers, and school management. Data analysis involved data reduction, display, and conclusion drawing, validated through source triangulation. Results indicate that the ARKA model is effectively implemented systematically as it aligns with the cognitive characteristics of elementary students. Based on field data, this model specifically yields a positive impact by increasing active participation and strengthening students' understanding of mathematical concepts. Initial time management challenges can be overcome with school system support. Ultimately, the ARKA model is relevant as an adaptive alternative strategy for basic mathematics learning, aligning with the principles of the Merdeka Curriculum.Keyword: Merdeka Curriculum; ARKA Model; Mathematics Learning; Conceptual Understanding; Lower Grade.